193. Evaluation of Severity Scores in Patients with Methicillin-Susceptible Staphylococcus aureus Bloodstream Infections. (4th December 2021) - Craig, Alexandra; Wagner, Jamie; Barber, Katie
Abstract: Background: Staphylococcus aureus bloodstream infections (BSIs) are associated with increased morbidity, mortality, and healthcare costs. Severity of illness scores help stratify critically ill patients and assist providers in making decisions. The quick Pitt (qPitt) score is a reliable predictor of mortality in patients with Gram-negative BSIs (AUROC 0.85); however, limited data exist for using the qPitt in methicillin-susceptible S. aureus (MSSA) BSIs. Methods: This retrospective cohort evaluated patients with MSSA BSIs. The primary outcome was the discrimination of the qPitt in predicting hospital mortality compared to the Pitt bacteremia score (PBS). Secondary outcomes were clinical failure and the predictive discrimination of the qPitt score in comparison to other severity scoring modalities. Categorical data were analyzed using chi-square test or Fisher's exact test. Continuous data were analyzed using Student's t-test or Mann-Whitney U. Predictive discrimination was determined by the area under receiver operating characteristic curve. Results: One hundred patients were included with the mean age of 52 years (p=0.84) and a BMI of 30 kg/m 2 . Males were predominant (70%). Mortality occurred in 13 patients who had more ICU admissions (92% vs. 37%; p< 0.01) and longer ICU LOS (10 vs. 5 days; p=0.03) despite similar baseline comorbidities. Time to definitive therapy was longer in the mortality group than non-mortality group (28 vs. 23 hours; p=0.79) though antimicrobial use did not differ. As outlined in Figure 1, the mortality group had higher severity of illness scores. The qPitt had a ROC of 0.83, indicating high discrimination. Overall, qPitt was found to be similarly predictive than PBS, equally as predictive as qSOFA, and more predictive than SIRS and APACHE II (Figure 1). Clinical failure occurred in 23% of patients; 54% of the mortality group experienced persistent BSI vs. 11% in the non-mortality group (p< 0.01), and 3% of the non-mortality group had recurrent infection (p=1.00). Conclusion: Compared to previous studies on Gram-negative BSIs, the qPitt performed similarly in MSSA BSIs. The qPitt can be considered for use in predicting mortality for patients with MSSA BSIs; however, further studies are needed to confirm these results. Disclosures: All Authors : No reported disclosures